Gain and phase errors calibration for joint time reversal and PCA dimensionality reduction over multipath environment - Fangwei LI; Jiawen LU; Mingyue WANG (Tongxin xuebao)
Aiming at the problem of inaccurate calibration of the array gain and phase errors caused by the signal source coherence in the multipath environment, a combination of time reversal (TR) and principal component analysis (PCA) calibration algorithm was proposed.The space-time synchronization focusing characteristic of TR was applied to obtain the return signal matrix of the target to suppress the multipath effect and reduce the signal source coherence.However, in view of the problem that the introduction of TR would make the dimension of the return signal matrix received by the array larger and increase the calculation complexity of the algorithm, PCA was utilized to implement dimensionality reduction reconstruction on the revised TR return signal matrix to reduce the computational complexity.The simulation results show that the proposed algorithm can effectively calibrate the gain and phase errors of the array with lower computational complexity in a multipath environment.